Politik Dinasti Pangeran Muhammad Arsyad - Sinta Nuriya; Izomiddin Izomiddin; Yulion Zalpa (Jurnal Prodi Ilmu Politik, 2023)
This study discusses the dynastic politics of the descendants of Prince Muhammad Arsyad and how the ability of the Muhammad Arsyad breed in terms of leading and managing the village of Tambang Rambang kec. Rambang Kuang kab. Ogan Ilir. The purpose of this study is to find out how dynastic politics can gain power and maintain power in the village of Tambang Rambang. In this study, the authors used descriptive qualitative research methods, by conducting observations at the research site and collecting data from images, texts and interviews. The formulation of the problem that the author proposes is: how is the politics of the dynasty of Prince Muhammad Arsyad and the ability to manage leadership in the village of Tambang Rambang? In order to answer these research questions, the author uses dynastic political theory and supporting theories, namely social capital and capital (economic) capital. The theory of dynastic politics is used to see how to gain and maintain power. The theory of social capital and capital is used as a tool to win every village head election in Tambang Rambang village. An important finding in this study is that to control the political stage in Tambang Rambang village it is not enough to have blood relations but must have the ability and strengthen the mastery of social capital. economy in the village. Keywords: Politics, Dynasty Politics